Mineralization and efficiency in the homogeneous Fenton Orange G oxidation - Doumic, Lucila Inés (2013)
This study focuses on the homogeneous Fenton oxidation ofthe synthetic azo-dye Orange G as a model compound. The impactofinitial TOC, hydrogenperoxide andcatalyst concentrations and of temperature on mineralization and efﬁciency in the use of hydrogen peroxide is addressed. Dissolved oxygen Concentration is monitored as an indication ofthe efﬁcient use of H2O2 in the process. A two-stage lumped kinetic model is proposed to address the effect of initial TOC, catalyst and oxidant concentrations and temperature ontotal organic carbonconsumption. Temperature increase and dosiﬁcationofthe oxidant are evaluated and compared as process intensiﬁcation strategies